Simulating multigun system with Langmuir law emission current - Martynenko, P.A. (Вопросы атомной науки и техники, 2018)
The results of numerical calculations of charged particle trajectories in a three-electrode structure are presented. A complex behavior is considered in the numerical calculations by the method of flow tubes of beams with a current limited by space charge. A method is given for choosing the relaxation parameter of the injector emission current at which after the completion of the transition process a stationary state is reached in the calculation.